THE EFFECTIVENESS OF GUESSING GAME TOWARDS STUDENTS’ WRITING SKILL ON DESCRIPTIVE TEXT - Safitri, .; Wijaya, Bambang; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The aim of this research is to investigate the effectiveness and the effect size of using Guessing Game in students’ writing skill on descriptive text. This research was conducted to the seventh grade students of MTS N 01 Pontianak in academic year 2014/2015. In this research, a pre-experimental design was used by the writer and the sample class VII C which consisted of 40 students. The writer used the measurement technique to collect the data and the tool of data collecting was written test. The result of data analysis, the writer found out that the effect size of the treatment was 1.47 and it was qualified as very strong effect. In conclusion, the effectiveness of the use of Guessing Game is very strong to improve the students’ writing skill on descriptive text. Keywords: Guessing Game, Writing skill, Descriptive Text Abstrak: Tujuan dari penelitian ini adalah untuk menginfestigasi keefektifan dan seberapa efektifnya penggunaan Guessing Game di keterampilan menulis siswa pada teks deskriptif. Penelitian ini dilakukan pada siswa kelas VII dari MTS N 01 Pontianak pada tahun ajaran 2014/2015.Dalam penelitian ini, penulis menggunakan desain pra-eksperimen dan kelas VII C yang terdiri dari 40 siswa sebagai sampel. Penulis menggunakan teknik pengukuran untuk mengumpulkan data dan alat pengumpulan data adalah tes tertulis. Hasil dari data analisis, penulis menemukan bahwa ukuran efek dari penanganan adalah 1,47 dan itu memenuhi syarat sebagai efek yang sangat kuat. Kesimpulannya, efektivitas dari penggunaan Guessing Game sangat kuat untuk meningkatkan kemampuan menulis siswa pada teks deskriptif. Keywords: Guessing Game,Menulis,Teks Deskriptif